Proposal and testing of a ‘risk-based’ framework for assessing reduction in consent monitoring requirements of closed landfills : a thesis presented in partial fulfilment of the requirements for the degree of Master of Health Science in Bioscience at Massey University, Wellington, New Zealand - Zhang, Hao (Massey University, 2026)
Legacy municipal landfills, closed before the implementation of contemporary engineering standards, represent a persistent potential source of long-term environmental contamination, particularly in groundwater-dependent regions. In New Zealand, numerous such sites, constructed without engineered liners or leachate management systems, may continue to impact groundwater resources decades after closure. This thesis investigates the current environmental risk posed by seven closed, unlined landfills within the Central Hawke’s Bay District and evaluates the ongoing justification for their groundwater monitoring regimes. To enable consistent and defensible assessment across multiple heterogeneous sites, a risk-based decision-making flowchart was developed and applied. This flowchart integrates the Source–Pathway–Receptor (S-P-R) model with a semi-quantitative, multi evidence assessment of hydrogeological setting, monitoring data, and receptor sensitivity. Risk classification is determined through converging lines of evidence, including statistical exceedance analysis (using UPL95 thresholds), inter-well comparisons (where possible), and evaluation of long-term contaminant trends in key monitoring parameters. Linear regression was applied to detect potential long-term trends in water quality, while t-tests assessed whether the mean concentrations of monitored parameters were significantly above or below nominated thresholds. All analyses were conducted on raw data, acknowledging potential variability introduced by analytical methods and seasonal influences, and any apparent outliers were carefully considered in context rather than automatically excluded. The application of this framework indicates that the majority of the assessed landfills exhibit stable or declining contaminant concentrations. This is consistent with their progression into late methanogenic or maturation phases, where leachate strength naturally attenuates. Key conservative indicators, such as chloride and potassium, were consistently within or close to the background range, while ammoniacal nitrogen and organic parameters (TOC, VFA, UV254) generally show either no trend or weakening signatures. Notably, some minor fluctuations and isolated higher measurements were observed at a few sites, likely reflecting short-term environmental variability, laboratory differences, or seasonal influences, but these did not represent sustained or significant changes in groundwater quality. Hydrogeological context is a critical moderating factor; several sites benefit from advantageous conditions such as river-adjacent dilution or hydraulic gradients that direct flow away from sensitive receptors. For example, downgradient monitoring bores at Waipawa, Tikokino, and Takapau are located over 2 km from the landfill footprint, which limits the potential for contaminant transport. In contrast, the Tamumu site exhibits shorter transport pathways and closer downgradient receptors, which correspond with detectable elevations, including total ammoniacal nitrogen exceeding the threshold limits and slightly elevated concentrations of TOC and UV254. Despite these elevated indicators, the concentrations remain below thresholds of human health concern, and the potential impact is partially mitigated by natural barriers such as the Tukituki River. In some cases, results are likely to reflect location and nearby land use factors. For example, higher than usual conductivity, ammoniacal nitrogen, and TOC are present at Porangahau closed landfill, consistent with soil chemistry in a coastal location. Across the seven landfills, the monitoring evidence can be broadly categorised into two behavioural groups. Six landfills (Waipawa, Waipukurau, Takapau, Tikokino, Ongaonga, and Porangahau) demonstrated low-risk characteristics, including no measurable downgradient enrichment, stable or declining concentrations, and chemical profiles consistent with natural background groundwater. Temporal trends were weak or absent, and t-tests consistently showed significant negative values, confirming compliance with nominated thresholds and reinforcing the conclusion that these sites exert minimal influence on surrounding groundwater quality. Tamumu represents a medium risk site, this classification is supported by upward trends in select parameters, shorter pathway distances, and the presence of downgradient receptors within 100 m. The analysis of these seven case-study landfills highlights the effectiveness of the risk based decision framework for synthesising disparate monitoring data into coherent, scientifically grounded risk assessments. By explicitly considering source characteristics, pathways, receptor alignment, and hydrogeological context, the framework allows for transparent classification of sites, supports the rationalisation of monitoring where appropriate, and provides defensible guidance for environmental management and regulatory compliance. Overall, the results demonstrate that, while some minor site specific variations exist, the dominant pattern across Central Hawke’s Bay’s legacy municipal landfills is one of long-term stability and generally low environmental risk, with the exception of a single site (Tamumu) at medium-risk profile.
Keywords: Legacy municipal landfills; Environmental risk assessment; Risk-based decision making framework; Source–pathway–receptor model; 410402 Environmental assessment and monitoring; 410604 Soil chemistry and soil carbon sequestration (excl. carbon sequestration science)